The Baing Yusuf Grand Mosque: A Symbol of Culture and Muslim Identity in Purwakarta - Alya Awwaliyatin Kuswandi; Amelia Fildza Ramadhani; Dania Widia Cahyani; Femy Geria Rohimah; Luthfia Chairun Nisa Putri Syahbana; Hisny Fajrussalam (UIN Imam Bonjol Padang, 2025)
The Baing Yusuf Grand Mosque plays a significant role in the history of Islamic dissemination and the formation of the local community's Islamic identity. This article discusses how Islam in Indonesia developed by adopting local culture without losing its fundamental teachings, aligning with Gus Dur's concept of Islam's Indigenization (Pribumisasi Islam). The mosque's architecture reflects a blend of Islamic culture and local traditions, featuring distinctive elements such as domes, calligraphy, and multi-tiered roofs characteristic of Javanese and Sundanese architecture. Beyond its function as a place of worship, the mosque has also served as a center for education, social activities, and dakwah (Islamic propagation) since its establishment by Syeikh Baing Yusuf in the 19th century. This research employed a literature review method to explore the historical, architectural, and social aspects of the mosque. The findings indicate that the Baing Yusuf Grand Mosque is not merely a religious symbol but also a continuously evolving hub of Islamic activity. It plays a vital role in building a strong Muslim community and has become a destination for religious tourism. Based on the findings from this literature review, it can be concluded that the Baing Yusuf Grand Mosque holds significant importance as a cultural and identity symbol for Muslims in Purwakarta.